Growth and population parameters of the world’s northernmost harbour seals (Phoca vitulina) residing in Svalbard, Norway - Kovacs, Kit M.; Lydersen, Christian (Norwegian Polar Institute, 2008)
The harbour seals (Phoca vitulina) in Svalbardare the northernmost population of this species. The population size is thought to be less than 1,000 individuals; these animals reside principally within a national park on Prins Karls Forland on the west coast of Spitsbergen, Svalbard, at about 78°20'N. The material presented in this study was collected from 367 live-captured animals. Upon capture, weight, standard length and girth were measured and a 50 ml blood sample taken. In adults, one of the lower incisors was extracted for age determination. Standard lengths, girths, and blood samples were also taken from a sub-sample of the pups, depending on the conditions surrounding the capture. All seals weretagged with a Rototag in each hind flipper before being released. Seals were aged based on growth layers read from stained, decalcified incisor sections (except for pups of the year). Age at sexual maturity was assessed based on analyses of sex hormones in blood plasma (testosterone in males, estradiol in females) using commercially available immunoassay kits.